Respostas
respondido por:
5
Resposta:
29/4
Explicação passo-a-passo:
x²-(2/3)x + 4
x= -3/2
x²-(2/3)x + 4 = (-3/2)² - (2/3)*(-3/2) + 4 = 9/4 - (-6/6) + 4 = 9/4 + 1 + 4 = 9/4 + 5 = (9*1 + 5*4)/4 = (9+20)/4 = 29/4
respondido por:
3
Na expressão x2 - (2/3)x + 4 :
x²- (2/3).x + 4 =
(-3/2)²-(2/3).(-3/2)+4=
(9/4)-(-6/12)+4=
(9/4)+(6/12)+4=
= 2,25+0,5+4
= 2,25+4,5
=6,3
=63/10
espero ter ajudado!
boa tarde!
KurtWagner:
Você errou amigo
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás